PROBLEMS OF FINANCING THE SOCIAL SPHERE FROM THE STATE BUDGET ОF UZBEKISTAN - Muyassar Mirzakarimova; Bakhtiniso Pardaeva (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The social sphere occupies an important place in the economic system of the country. For the rapid development of the social sphere, it is necessary to stimulate the priority allocation of funds to this sphere. Budget funds are the main source of funding for socio-cultural activities. Budget spending on the social sphere serves as a financial guarantee for the use of social services by citizens of the country at the required level. The purpose of this article is to develop a scientific proposal and practical recommendations for improving the mechanism for financing the social sphere from the budget through the correct distribution of powers between local budgets.